The Role of Microtubule Associated Serine/Threonine Kinase 3 Variants in Neurodevelopmental Diseases: Genotype-Phenotype Association - Shu, Li; Xiao, Neng; Qin, Jiong; Tian, Qi; Zhang, Yanghui; Li, Haoxian; Liu, Jing; Li, Qinrui; Gu, Weiyue; Wang, Pengchao; Wang, Hua; Mao, Xiao (Frontiers in Molecular Neuroscience, 2022)
Objective To prove MAST3 gene is associated with neurodevelopmental diseases (NDD) and the genotype-phenotype correlation. Methods Trio exome sequencing was performed on four NDD trios. Bioinformatic analysis was conducted based on large-scale genome sequencing data and human brain transcriptomic data. Further in vivo zebrafish studies were performed. Results In our study, we identified four de novo MAST3 variants (NM_015016.1: c.302C>T:p.Ser101Phe; c.311C>T:p.Ser104Leu; c.1543G>A:p.Gly515Ser; c.1547T>C:p.Leu516Pro) in four DEE patients separately. Clinical heterogeneities were observed in patients carrying variants in DUF and STK domain separately. Using published large-scale exome sequencing data, higher CADD scores of missense variants in DUF domain were found in NDD cohort compared to gnomAD database. We also obtained an excess of missense variants in DUF domain when compared autistic spectrum disorder (ASD) cohort to gnomAD database, similarly an excess of missense variants in STK domain when compared DEE cohort to gnomAD database. Based on Brainspan datasets, we showed that MAST3 expression was significantly up-regulated in ASD and DEE-related brain regions and was functionally linked with DEE genes. In zebrafish model, abnormal morphology of central nervous system was observed in mast3a/b crispants. Conclusion Our results support the possibility that MAST3 is a novel gene associated with NDD which could expand the genetic spectrum for NDD. The genotype-phenotype correlation may contribute to future genetic counselling.